Lets reveal it: what are learning obstacles in combinatorial problems - G D Nugraha; E Mulyana; D Suryadi (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Combinatoric problems usually raises a contextual problems in our daily life and needs a deep understand for solving it. This article tells about exploring what are the learning obstacles in Combinatoric Problems. The author use a diagnostic test to observe what is the learning obstacles in combinatoric problems. The author gave the test to 15 students who already learned this topic and they answered questions from three different problems. At the end, they have to find what are the differences from that third situation. The results were they could be understand the situation and solved the problem. the conclusion was none of learning obstacles that found but it is a few things that should be noted for the author. First, how to make a better learning materials and learning situation. Second, how to develop and to increase the student conceptual understanding so they can analyze every problem comprehensively.This paper as a part of Didactic Design Research.